Social Sciences, asked by oviyantan07, 3 months ago

TF!!!
written solution please!
(╥﹏╥)​

Attachments:

Answers

Answered by shivangisaxena20
1

Answer:

 { \frac{2}{3} }^{x - 1} =  { \frac{2}{3} }^{2 - x } \\  \\  =  > x - 1 = 2 - x \\  =  > x + x = 2 + 1 \\  =  > 2x = 3 \\  =  > x =  \frac{2}{3}

 ({3}^{ - 1}  -  {5}^{ - 1})^{ - 1}   \div ( {2}^{ - 1}  -  {3}^{ - 1} ) ^{ - 1}  \\  =  > ( ({a}^{b}) ^{c}  =  {a}^{bc} by \: applying  \: this \: law \: ) \\  =  > ( {3}^{ - 1 \times  - 1}  -  {5}^{ - 1  \times  - 1} ) \div ( {2}^{ - 1 \times  - 1}  -  {3}^{ - 1  \times  - 1} ) \\   =  > ( {3}^{1} -  {5}^{1}  ) \div  ({2}^{1}  -  {3}^{1} ) \\   =  > ( - 2) \div  (- 1) \\  =  > 2

hope it helps

Similar questions